Nadomestni habitat - omilitveni ali izravnalni ukrep? - Klemenčič, Tina (Varstvo narave, 2015)
The Nature Conservation Act stipulates certain mitigation and compensatory measures, with which an encroachment upon nature or its impacts are mitigated, or with which the envisaged or already caused degradation of nature is compensated. Among the possible types of these measures is introduction of replacement habitat, which has the same nature-conservation characteristics as the area significantly impacted by encroachment. On the basis of experience gained in Slovenian nature conservation practice and following the European law cases in other countries, the present article discusses the question whether the replacement habitat is a mitigation measure or a compensatory measure. The European legislation practice has made it clear that the European Commission stands proxy for the standpoint that replacement habitat in Natura 2000 area cannot serve as a mitigation measure but is used, after the implemented procedure of imperative reasons of overriding public interest, as a compensatory measure in the sense of Paragraph 4 of Article 6 of the Habitats Directive. This, however, is feasible only when the following three conditions are met: that no other alternatives exist to attain the plan's or project's objectives (1), that imperative reasons of overriding public interest (over the public interest of nature conservation) exists (2), and that compensatory measures, which will provide for the preservation of integrity and connectivity of the Natura 2000 network, will be implemented (3).
Keywords: evropska sodna praksa; izravnalni ukrepi; nadomestni habitati; Natura 2000; obvoznice; omilitveni ukrepi; Škofljica